2021
DOI: 10.3389/fpsyt.2021.675237
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Gaming and Sleep: A Systematic Review and Meta-Analysis

Abstract: Problematic gaming has been linked to poor sleep outcomes; however, these associations have not yet been synthesized quantitatively. This review employed a meta-analysis to investigate the relationship between problematic gaming and sleep-related outcomes. A search of Medline, Embase, Web of Science, PsycINFO, and Google Scholar identified a total of 763 studies, including 34 studies (n = 51,901 participants) eligible for inclusion. Papers were included if available in any European language, addressed problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 102 publications
(130 reference statements)
3
32
1
Order By: Relevance
“…However, no studies have looked at technology use and social jetlag defined as a difference in bedtime on weekdays and weekends [19]. Moreover, a recent literature review found that problematic gaming was associated with shorter sleep duration, increased likelihood of reporting poor sleep quality, daytime sleepiness, and sleep problems [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have looked at technology use and social jetlag defined as a difference in bedtime on weekdays and weekends [19]. Moreover, a recent literature review found that problematic gaming was associated with shorter sleep duration, increased likelihood of reporting poor sleep quality, daytime sleepiness, and sleep problems [39].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previously published meta-analyses of cross-sectional studies, IA can be associated with a wide range of social and mental issues such as substance abuse, depression, anxiety, poor sleep quality, and attention deficit hyperactivity disorder (ADHD); however; the association remains to be further investigated and clarified [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reports have prompted growing awareness and concern regarding the adverse health risks associated with excessive gaming (Holden et al, 2018). In particular, gaming is associated with longer sleep onset latency, short sleep duration, and poor sleep quality (Kristensen et al, 2021). There is also evidence describing altered sleep architecture from gaming, including reduced slow-wave sleep and rapid eye movement sleep (Higuchi et al, 2005;Dworak et al, 2007;Weaver et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances may also manifest as sleep disorders, such as insomnias, and challenge the initiation and maintenance of healthy sleep. This could provoke problematic gaming behaviors, whereby gamers displace sleep with gaming activities as a way of coping with their sleeplessness (Kristensen et al, 2021). A vicious cycle may thus ensue, in which unhealthy sleep practices and problematic sleep perpetuate problematic gaming behaviors (Kristensen et al, 2021), translating to profound acute and chronic implications on cardiometabolic health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation